Avaliação das concentrações hepáticas e séricas de retinol em bovinos e do consumo habitual de fígado por gestantes - Aquino, Rose Cléia Praxedes de (2005)
The vitamin A is essential to animals because of its participation in a great number of biological functions. The investigation of this vitamin s concentrations is important to serve as reference to normality parameters. This study had as aim to analyse the serics and hepatics concentrations of vitamin A in two groups of bovines and to compare the hepatics concentrations to the present requeriments of vitamin A for pregnant women. It was also appraised the consume habit of bovine liver by pregnant women through of the alimentary frequency quest. Two groups of bovine were studied and the first was formad by Nelore bovine breed and the second by bovine without defined breed (WDB). It was analysed 120 samples: 60 of liver and 60 of serum. The method used to dose retinol was High Performance Liquid Cromatography (HPLC). The average (+ sd) of retinol concentrations in Nelore breed bovine and WDB liver were 16947,8 + 6866,9 and 5213,1 + 2517,2 µg of retinol/100g and at serum 39,6 + 17,9 e 28,6 + 9,4 µg of retinol/dL, respectively. No statistically significant correlation was found between hepatic and the serum retinol. The bovines in this study had adequate vitamin A levels. Independently of animal breed, the daily ingestion of bovine liver is not advised for pregnant women who show adequate support of vitamin A. The consume of bovine liver by pregnant women consulted on school maternity hospital Januário Cicco, UFRN, Natal RN, was considered high